Functional Specialization of Cellulose Synthase Isoforms in a Moss Shows Parallels with Seed Plants. Issue 1 (2nd August 2017) - Norris, Joanna H.; Li, Xingxing; Huang, Shixin; Van de Meene, Allison M.L.; Tran, Mai L.; Killeavy, Erin; Chaves, Arielle M.; Mallon, Bailey; Mercure, Danielle; Tan, Hwei-Ting; Burton, Rachel A.; Doblin, Monika S.; et al.
Abstract : Regulatory uncoupling of primary and secondary cellulose synthases occurred independently in mosses and seed plants and is associated with convergent evolution of secondary wall structure. Abstract: The secondary cell walls of tracheary elements and fibers are rich in cellulose microfibrils that are helically oriented and laterally aggregated. Support cells within the leaf midribs of mosses deposit cellulose-rich secondary cell walls, but their biosynthesis and microfibril organization have not been examined. Although the Cellulose Synthase ( CESA ) gene families of mosses and seed plants diversified independently, CESA knockout analysis in the moss Physcomitrella patens revealed parallels with Arabidopsis ( Arabidopsis thaliana ) in CESA functional specialization, with roles for both subfunctionalization and neofunctionalization. The similarities include regulatory uncoupling of the CESAs that synthesize primary and secondary cell walls, a requirement for two or more functionally distinct CESA isoforms for secondary cell wall synthesis, interchangeability of some primary and secondary CESAs, and some CESA redundancy. The cellulose-deficient midribs of ppcesa3/8 knockouts provided negative controls for the structural characterization of stereid secondary cell walls in wild type P. patens . Sum frequency generation spectra collected from midribs were consistent with cellulose microfibril aggregation, and polarization microscopy revealed helical microfibril orientation only in wild type leaves. Thus, stereid secondary walls are structurally distinct from primary cell walls, and they share structural characteristics with the secondary walls of tracheary elements and fibers. We propose a mechanism for the convergent evolution of secondary walls in which the deposition of aggregated and helically oriented microfibrils is coupled to rapid and highly localized cellulose synthesis enabled by regulatory uncoupling from primary wall synthesis.